Words & Occasions - Pearson, Lester B. (Book collections on Project MUSE., 1970)
A portrait in words of Lester Pearson, this volume contains his own selection of his speeches and writings from 1924 to 1968 on a wide variety of topics - serious and frivolous, political and non-political - with introductions which serve as an autobiographical and interpretative link carrying the reader forward through his career.